Leadership in Action Dividends and interest--The Last Leadership Guru - Wilcox, Martin (Center for Creative Leadership, 2007)
Everyone is an expert on leadership. Each one of us, every day, is deeply involved in its practice. At work, at home, and in our various communities-anytime there is a situation to be evaluated and a decision to be made and followed up on-we are participating in leadership.
Title from content provider
Keywords: Leadership